P506 Incidence risk of colorectal cancer, non-melanoma skin cancers and non-Hodgkin lymphoma in Japanese patients with ulcerative colitis based on large-scale claims database. (16th January 2018) - Kobayashi, T; Uda, A; Mineyama, T; Udagawa, E; Iwasaki, K; Tang, W; Hibi, T
Abstract: Background: Patients with ulcerative colitis (UC) have been reported about not only a higher incidence of colorectal cancer (CRC) compared with general population, but also increased risks of non-melanoma skin cancers (NMSC) and non-Hodgkin lymphoma (NHL) associated with immunosuppressive drugs such as thiopurines in Caucasians. However, there is no such study in Asian patients with UC based on large-scale real-world data, except for one questionnaire survey which reported similar incidence of lymphoma in Japanese patients treated with thiopurines. Therefore, we conducted an exploratory analysis of the overall incidence risks of malignancies in Japanese UC patients, and also UC patients who used thiopurines and anti-tumour necrosis factor (TNF) agents, using large-scale claims database. Methods: Japan Medical Data Center (JMDC) database, which contains 3 869 105 people from 2005 to 2016 was used for the analysis. Patients with at least one diagnosis of UC (ICD10: K51) were identified from the database. Treatment-related incidences of CRC, NMSC, and NHL were identified according to their ICD10 codes if they happened after the prescription of thiopurines and/or anti-TNF agents, without considering exposure time to drugs. Age- and sex-adjusted incidence ratio (IR) in UC patients was calculated relative to the general population. Results: A total of 10 226 UC patients (mean age: 40.4 years old) were identified from JMDC database. During the mean observation period of 29.3 months, numbers of UC patients who developed CRC, NMSC, and NHL were 148 (1.4%), 7 (0.1%), 25 (0.2%), respectively. Compared with the general population, UC patients were observed with an increased overall incidence of CRC (IR, 7.55; 95% CI 6.34–8.77), NMSC (IR, 4.14; 95% CI 1.07–7.2) and NHL (IR, 4.61; 95% CI 2.81–6.42). The risks of these malignancies have no tendency to increase in patients with UC who were on thiopurines or anti-TNF (Table). Conclusions: This study tried to first assess the risks of malignancies in Japanese patients with UC based on large-scale real-world data. Risks of malignancies were found to be higher in UC patients than the general population, while no significant difference was shown between the overall UC patients and UC patients on thiopurines and/or anti-TNF agents. It suggests that racial differences should be included in the individualised risk-benefit consideration for UC management. It should also be noticed that the part of claims data is yet to be fully validated and further analysis adjusting more factors with longer observation period is needed.